The last card inside George W. Bush's decision to surge in Iraq - Sayle, Timothy A.; Engel, Jeffrey A. 1972-; Brands, Hal 1983-; Inboden, William 1972- (Cornell University Press, 2019)
"An oral history of President George W. Bush's decision to surge troops to Iraq, accompanied by scholarly analysis by leading scholars of international security and presidential history"--
Keywords: Iraq War, 2003-2011 / Decision making; Iraq War, 2003-2011 / Campaigns; Geschichte 2003-2007; Counterinsurgency / Iraq / History; Military planning / United States; Golfkrieg -- 2003; Militärpolitik; Widerstand; United States / Military policy / Decision making; Iraq / Politics and government / 2003-; Irak; USA; Aufsatzsammlung